OPTIMIZING TENSILE STRENGTH AT MAG WELDING PROCESS OF S235JR STEEL (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The article is of an experimental nature for welding S235JR by MAG welding method. The purpose of this work is to optimize the welding parameters of MAG welding using shield two-component gas cargon 18 to achieve ultimate tensile strength. The experiment is according to central composition design and 13 experiments were made. Samples with dimensions of 100x40x4 mm were tested with a universal tension-compression machine. Statistical processing was done and a regression relationship between welding current and seam width on the maximum tensile strength was obtained.